Benjamin D. Koen (ed.), The Oxford Handbook of Medical Ethnomusicology (2008) - Edwards, Jane (Journal of the Society for Musicology in Ireland, 2010)
Review of Benjamin D. Koen (ed.), The Oxford Handbook of Medical Ethnomusicology (Oxford: Oxford University Press, 2008), ISBN 978-0-19-533707-5